2008
DOI: 10.1007/s10750-008-9624-5
|View full text |Cite
|
Sign up to set email alerts
|

Should only live diatoms be used in the bioassessment of small mountain streams?

Abstract: It is unclear whether differentiating live and dead diatoms would enhance the accuracy and precision of diatom-based stream bioassessment. We collected benthic diatom samples from 25 stream sites in the Northern Oregon Coast ecoregion. We counted live diatoms (cells with visible chloroplasts) and then compared the counts with those generated using the conventional method (clean counts). Non-metric multidimensional scaling (NMDS) showed that the diatom assemblages generated from the two counts were overall simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Our results highlighted the importance to include in the sampling process also those areas where water velocity is null. Even though the collection of diatoms from depositional zones implicates the inclusion of dead frustules in the samples, it has been demonstrated that this does not affect the reliability of the diatom indices final score (Gillett et al, 2009;Barthès et al, 2014). The sampling of lentic MHs leads also to the inclusion of an important component of the community that would be otherwise underestimated, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlighted the importance to include in the sampling process also those areas where water velocity is null. Even though the collection of diatoms from depositional zones implicates the inclusion of dead frustules in the samples, it has been demonstrated that this does not affect the reliability of the diatom indices final score (Gillett et al, 2009;Barthès et al, 2014). The sampling of lentic MHs leads also to the inclusion of an important component of the community that would be otherwise underestimated, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Low contribution may be associated with relatively fast moving water and lack of major dams/reservoirs along the mainstem rivers. Discerning live from dead benthic diatoms in each assemblage may help identify resident from washed-in and dead benthic taxa in an assemblage (Gillett et al, 2009). Diatom analysis focusing on the live portion of the benthic assemblage may better elucidate the relationships between diatom assemblages and environmental conditions in large river littoral zones.…”
Section: Nitzschiamentioning
confidence: 99%
“…Boxes are inter-quartile ranges, lines are medians, whiskers indicate 10th and 90th percentiles, and circles are outliers. P-values are from two-sample t-tests for significant differences between impairment categories conducted separately on EHS and MHS diatoms in riffle and depositional habitats have been debated (Cox, 1998;Round, 1998;Gillett et al, 2009). However, research has shown that relationships of diatom assemblages with environmental gradients are similar regardless of correcting diatom counts for the number of dead diatoms (Gillett et al, 2009).…”
Section: Similarity Between Mhs and Ehsmentioning
confidence: 99%
“…P-values are from two-sample t-tests for significant differences between impairment categories conducted separately on EHS and MHS diatoms in riffle and depositional habitats have been debated (Cox, 1998;Round, 1998;Gillett et al, 2009). However, research has shown that relationships of diatom assemblages with environmental gradients are similar regardless of correcting diatom counts for the number of dead diatoms (Gillett et al, 2009). Also, some research has shown that including dead diatoms in counts provides greater integration of the temporal and spatial variations in environmental variables (Stevenson & Pan, 1999).…”
Section: Similarity Between Mhs and Ehsmentioning
confidence: 99%